(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the role of women in modern society and the importance of gender equality for social development. In many countries, women actively participate in education, professional life, and social activities, which significantly contributes to the progress of society. However, despite many positive changes, gender inequality and discrimination against women still remain important issues in some parts of the world. The purpose of this article is to analyze the role of women in society and to highlight the importance of ensuring equal rights and opportunities for both men and women. The study also discusses the participation of women in education, family life, and economic development. Achieving gender equality is essential for building a fair, stable, and progressive society. Supporting women’s rights and opportunities can lead to stronger communities and sustainable social development.